Between equality and efficiency in medical care - Zúñiga Fajuri, Alejandra (Acta Bioethica, 2008)
This work considers the allocation methods of scarce medical resources budgeted for "health economics". Costbenefit models and the criteria QALY (Quality-Adjusted Life-Years) are analyzed as allocation methods that propose to resolve ethical dilemmas related to an economic distribution that seems to prioritize efficient results over more equitable, but inefficient, results.